2020
DOI: 10.3389/fonc.2020.551668
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Based on Systemic Immune Inflammation Index and Prognostic Nutrition Index Predicts Recurrence of Hepatocellular Carcinoma After Surgery

Abstract: Background Surgery is a potential cure for hepatocellular carcinoma (HCC), but its postoperative recurrence rate is high, its prognosis is poor, and reliable predictive indicators are lacking. This study was conducted to develop a simple, practical, and effective predictive model. Materials and Methods Preoperative clinical and postoperative pathological data on patients with HCC undergoing partial hepatectomies at the Third Affiliated Hospital of Soochow University fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…Despite the improvement of therapeutic strategies and surveillance plans, the postoperative recurrence rate of HCC is still high and strongly associated with poor prognosis. A series of studies have reported that AFP levels and satellite nodules are related to worse survival of liver cancer patients (25)(26)(27). These results were similar in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the improvement of therapeutic strategies and surveillance plans, the postoperative recurrence rate of HCC is still high and strongly associated with poor prognosis. A series of studies have reported that AFP levels and satellite nodules are related to worse survival of liver cancer patients (25)(26)(27). These results were similar in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Tumor differentiation has been used to predict the prognosis of malignant tumors; however, recent studies revealed the lack of significant prognosis effect of tumor differentiation. 39 , 40 Several serum markers, such as prognostic nutritional index, 41 rapid turnover proteins (RTPs), 42 and some inflammation indicators, like systemic immune inflammation index (SII), 43 neutrophil-to-lymphocyte ratio (NLR), 44 lymphocyte-to-monocyte ratio (LMR), 45 and platelet-to-lymphocyte ratio (PLR) were found to contribute to tumor progression. 46 However, only a few studies compared AUC with other prognostic systems, such as TNM stage and Child-Pugh classification.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of known biomarkers in prognosis of PC is still controversial. The systemic immune-inflammation index (SII), a systemic inflammatory marker based on the counts of platelets (PLTs), neutrophils, and lymphocytes, has been linked to the outcomes of melanoma patients (5,6) and subsequently confirmed in patients with hepatocellular carcinoma (7)(8)(9)(10) and lung cancer (5). High SII is associated with shorter overall survival (OS) (11,12).…”
Section: Introductionmentioning
confidence: 99%